Eu2+ ions as an antioxidant additive for Sn-based perovskite light-emitting diodes. Issue 36 (9th September 2021) - Wang, Xi; Liu, Lihua; Qian, Zhao; Gao, Congcong; Liang, Hongyan
Abstract : We introduced Eu 2+ ions as the electron donor to provide a reducing environment to suppress the oxidation of Sn 2+ . Finally, we obtained a pure red (PEA)2 SnI4 LED with a high EQE up to 1.48% and a maximum brightness of 221 cd m −2 . Abstract : Sn-Based perovskite materials are environmentally benign and have low toxicity with excellent light emitting ability, and are ideal choices for light-emitting diode (LED) active layers. However, the tendency of Sn 2+ to be oxidized to Sn 4+ leads to increased crystalline defects and chemical instability, which hamper the external quantum efficiency of LEDs. Herein, we introduce Eu 2+ ions as the electron donor to provide a reducing environment to suppress the oxidation of Sn 2+, and as a stabilizer to adjust the growth of the perovskite film simultaneously. Techniques such as X-ray photoelectron spectroscopy, transient absorption, and scanning electron microscopy have confirmed that Eu 2+ ion doping can increase the film quality and decrease the Sn 4+ defect density. Benefiting from these merits, the LED based on (PEA)2 SnI4 film emits pure-red radiation with a maximum brightness of 221 cd m −2 and a high EQE up to 1.48%.